Texturing and modeling : a procedural approach. - Ebert, David S., 1964-; Musgrave, F. Kenton, ....-; Peachey, Darwyn, ....- (Amsterdam : Morgan Kaufmann, 2003)
The third edition of this classic tutorial and reference on procedural texturing and modeling is thoroughly updated to meet the needs of today's 3D graphics professionals and students. New for this edition are chapters devoted to real-time issues, cellular texturing, geometric instancing, hardware acceleration, futuristic environments, and virtual universes. In addition, the familiar authoritative chapters on which readers have come to rely contain all-new material covering L-systems, particle systems, scene graphs, spot geometry, bump mapping, cloud modeling, and noise improvements. There are many new spectacular color images to enjoy, especially in this edition's full-color format.
Keywords: Computer graphics; Visualisatietechnieken